Crowdfunding on Financial Well-Being in Micro, Small and Medium Enterprises (MSMEs) - Mohammad Ihsan; Firmansyah Firmansyah; Rista Aldilla Syafri; Ade Perdana Siregar (Pt. Anagata Sembagi Education, 2025)
The role of MSMEs in Indonesia is expected to improve welfare for society by contributing to Gross Domestic Product (GDP). MSMEs in Indonesia have the largest number in ASEAN countries, but the contribution of MSMEs to Gross Domestic Product (GDP) is still below other countries with fewer MSMEs. The biggest factor hindering MSMEs in their business is capital problems. Technology-based innovation by distributing profits according to the composition of capital provided is called equity crowdfunding. The level of achievement of financial well-being in a business organization is based on a person's initial goal for doing business which is referred to as business financial orientation. This research answers problems based on existing facts regarding the financial well-being of MSMEs. This type of research is research using quantitative methods, namely by testing the influence of the variables in this research. This research tests the relationship or influence by connecting and providing an explanation of the phenomena related to this research. The measurement method uses Structural Equation Modeling with the use of SmartPLS software data processing tools